Sensory characteristics of loins from pigs fed glycerol and ractopamine HCl during the last 28 days of finishing - Duttlinger, A.W.; Houser, Terry A.; Tokach, Michael D.; Dritz, Steven S.; Prusa, K.J.; Huskey, L.; DeRouchey, Joel M.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Sensory characteristics were evaluated on a total of 80 loins from pigs fed diets containing glycerol, ractopamine HCl (RAC), and a combination of glycerol and RAC during the last 28 d prior to harvest. A total of 1,054 pigs were blocked by weight and randomly allotted to 1 of 4 dietary treatments with 10 replications per treatment. Pigs were fed corn-soybean meal-based diets. Dietary treatments were arranged in a 2 × 2 factorial design with main effects of glycerol (0% or 5%) and RAC (0 or 6.75 g/ton). Pork loins from 1 randomly selected barrow and gilt from each pen were used for sensory analysis. There were no glycerol × RAC interactions or main treatment effects for cooking loss or Warner-Bratzler shear force (WBSF). Additionally, there were no glycerol × RAC interactions or main treatment effects for the sensory traits including myofibrillar tenderness, overall tenderness, pork flavor intensity, or off-flavor intensity. There was a glycerol × RAC interaction (P < 0.01) for the sensory trait of connective tissue amount. The interaction was a result of increased connective tissue amounts when glycerol was added to the diet without RAC but numerically decreased amounts when glycerol was fed in combination with RAC. In conclusion, feeding dietary glycerol or RAC singularly or in combination for 28 d prior to slaughter did not influence sensory characteristics of center-cut pork loin chops.
Keywords: Glycerol; Ractopamine HCl; Sensory analysis; Swine